Identifying Studentsâ Errors on Fractions - Lestiana, Herani Tri; Rejeki, Sri; Setyawan, Fariz (Universitas Muhammadiyah Surakarta, 2016)
Many studies have revealed that fraction is a complicated mathematics topic for students. Students struggle to solve problems including comparison and addition of fractions correctly. However, some students often make some common mistakes in solving the mathematics problems. There are three types of errors in solving mathematics problems, which are factual error, procedural error, and computational error. This study was aimed at investigating various mistakes by students in problems related to fractions. A set of validated problems about comparing and adding fractions was assigned to third grade students of SD N Laboratorium Unesa Surabaya. The results indicated that some students were not aware on how to compare and add fractions. Most of these students employed incorrect strategies categorized as procedural and conceptual errors.